From eye to heart exterior spaces explored and explained - Burley, Jon; Machemer, Patricia (Cognella Academic Publishing, 2016)
"From eye to heart: exterior spaces explored and explained blends science, art, theory, and history to survey environmental design across significant cultures and places. Based on extensively class-tested material and the joint experiences of the authors as planners, designers, artists, and scientists, From Eye to Heart has a global perspective on the spaces humans create"-- Provided by publisher.